Atypical Cases of Leptospirosis: Insights From Georgia - Arash Ghani Dehkordi; Salah Rabea Salah Al-Tamary; Ashraf Rabea Salah Al-Tamary; Hamza Rabea Salah Al-Tamary; Shams Samih Ahmad Albarari; Alaaldin Mohammad Zeyad Assad; Ghena Mohammad Othman Hamdan; Ia Mikadze (Case Reports in Infectious Diseases)
Pathogenic Leptospira species are the source of leptospirosis, a common zoonotic infection that can cause a wide range of clinical manifestations, from minor flu-like symptoms to severe multiorgan failure. We present two peculiar cases of leptospirosis; they highlight the need for clinical awareness to improve patient outcomes and further knowledge of leptospirosis epidemiology and therapy by illuminating the difficulties in diagnosis and treatment. The first case involved a 30-year-old male presented with jaundice. Although he had no history of chronic illnesses, an exhaustive investigation was warranted due to his recent travel history and occupational contact. Laboratory tests revealed significantly increased levels of AST and ALT and positive Leptospira IgM serology. Remarkably, the patient refuted the traditional theory of leptospirosis transmission by denying direct animal interaction. After starting therapy with dexamethasone initially and adding doxycycline later, the patient’s condition significantly improved; his jaundice resolved and his liver enzyme levels returned to normal. An outpatient follow-up after discharge was advised to assess liver and kidney function. The second case involved an 87-year-old woman with a fever, weakness and hypertension. Investigations revealed hepatosplenomegaly, raising the possibility of hypersplenism. She reported exposure to animals, particularly her dogs in her urban house. Surprisingly, her AST and ALT levels were normal. Lab tests also revealed thrombocytopoenia with normal APTT and prolonged PT. Serological tests indicated positive Leptospira IgM. Along with intravenous infusions, the patient’s treatment plan comprised dexamethasone, enalapril and ceftriaxone to treat inflammation, hypertension and bacterial infection, respectively. Following a 20-day hospital stay, the patient’s laboratory results and symptoms improved, leading to her discharge. Continuous follow-up recommended to monitor her recovery and prevent recurrence. These case studies emphasise the significance of taking leptospirosis into account when treating patients who do not have normal exposure histories yet present with unusual symptoms.